18.2k views
0 votes
Please help me....I really need help!!

Which expression is equal to
(cx^(2)-4 )/(6c^(4)+15c^(3) ) ÷
(c^(2) +4c+4)/(12c^(3)+30c^(2) ) ?

A.
(2(c-2) )/(c(c-2))
B.
(2(c-2))/(c(c-2))
C.
(c(c+2))/(2(c+2))

User Liakoyras
by
5.6k points

1 Answer

3 votes


(c^2-4)/(6c^4+15c^3)/(c^2+4c+4)/(12c^3+30c^2)=(c^2-2^2)/(3c^3(2c+5))/(c^2+2(c)(2)+2^2)/(6c^2(2c+5))\\\\_{\text{use}\ a^2-b^2=(a-b)(a+b)\ \text{and}\ (a+b)^2=a^2+2ab+b^2}\\\\=((c-2)(c+2))/(3c^3(2c+5))\cdot(6c^2(2c+5))/((c+2)^2)=((c-2))/(c)\cdot(2)/((c+2))=\boxed{(2(c-2))/(c(c+2))}

User Heikura
by
6.1k points